Using the Balance Sheet Approach in Surveillance : Framework and Data Sources and Availability - Mathisen, Johan (International Monetary Fund, 2007)
A distinguishing feature of emerging market crises in recent years has been the sudden disruption in the capital accounts of the economy. These crises have highlighted the need for closer attention to macroeconomic vulnerabilities in sectoral balance sheets. This book enhances application of the balance sheet approach to surveillance by taking advantage of new data sets that provide detailed, frequent, and timely financial statistics.